2016
DOI: 10.25103/jestr.096.17
|View full text |Cite
|
Sign up to set email alerts
|

Method of Analysis and correction of the Error from Nonlinearity of the Measurement Instruments

Abstract: In this work are examined the characteristics of the error from nonlinearity of the static characteristic of the measuring instruments. The possibilities to correct this error are analyzed. Mathematical models are presented, in order to allow evaluation of the error from nonlinearity regarding the permissible error of the measurement result, as well as to draw the necessary algorithms for correction of this error. The models are developed, based on the method of the smallest modules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…where: 𝑧𝑧 π‘˜π‘˜ and 𝑧𝑧 π‘˜π‘˜ β€² are the confocal parameters of the beam before and after the collimating system. Expression (6) shows that in order to reduce the divergence it is necessary that 𝑀𝑀𝑀𝑀 < 1 . This is achieved by proper selection of the focal lengths 𝑓𝑓 1 β€² and 𝑓𝑓 2 β€² , which results in the required ratio between the confocal parameters of the beam, which in turn causes a decrease in the divergence and an increase in the size of the beam waist after the collimating system.…”
Section: Development Of a Two-component Collimating Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…where: 𝑧𝑧 π‘˜π‘˜ and 𝑧𝑧 π‘˜π‘˜ β€² are the confocal parameters of the beam before and after the collimating system. Expression (6) shows that in order to reduce the divergence it is necessary that 𝑀𝑀𝑀𝑀 < 1 . This is achieved by proper selection of the focal lengths 𝑓𝑓 1 β€² and 𝑓𝑓 2 β€² , which results in the required ratio between the confocal parameters of the beam, which in turn causes a decrease in the divergence and an increase in the size of the beam waist after the collimating system.…”
Section: Development Of a Two-component Collimating Systemmentioning
confidence: 99%
“…It is assumed that the type of the laser and its parameters are known: πœ†πœ†, πœ”πœ” 0 = πœ”πœ” 1 , πœƒπœƒ = πœƒπœƒ 1 , π‘Ÿπ‘Ÿ π‘˜π‘˜ = π‘Ÿπ‘Ÿ π‘˜π‘˜1 . The design of the two-component collimating system was developed in the following sequence: a) Determining the angular magnification 𝑀𝑀𝑀𝑀 by expression (6).…”
Section: Development Of a Two-component Collimating Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the 20-years experience of the authors and over 60 publications on the problems of the asymmetrical profile, it has been found that a major problem in its use is the reversal of the direction of movement [1,2,3]. As a solution, the authors set out [4,5] a basic principle of interlocking, allowing the making of gears with an unachievable until now quality and strength indicators [12]. On the basis of the implications of this principle, three approaches have been developed for geometric synthesis and realization of unconditional areas of existence in the field of independent variables.…”
Section: Introductionmentioning
confidence: 99%
“…This complicated model for reproducing the direction of the vertical leads to a number of disadvantages such as a complex design resulting in a bigger instrumental error, low reliability under extreme conditions, need for special systems ensuring the operation of the gyro-vertical, larger dimensions, higher price of the instrument or system, etc. [9], [10].…”
Section: Introductionmentioning
confidence: 99%